Resveratrol‐Loaded Poly(d, l‐Lactide‐Co‐Glycolide) Microspheres Integrated in a Hyaluronic Acid Injectable Hydrogel for Cartilage Regeneration. Issue 1 (22nd October 2021) - Wang, Xi; Li, Xiaolin; Duffy, Patrick; McMahon, Sean; Wang, Xianqing; Lyu, Jing; Xu, Qian; A, Sigen; Chen, Ningyi N.; Bi, Vivian; Dürig, Thomas; Wang, Wenxin
Abstract : Cartilage tissue has a relatively low regenerative capacity which leads to a need for disease‐modifying active pharmaceutical ingredients (APIs) which can stimulate its regeneration and more urgently, effective ways of introducing APIs into the cartilage defects. Herein, an integrated system is proposed in which a hyaluronic acid (HA)‐based injectable hydrogel scaffold is embedded with API‐loaded poly(d, l ‐lactide‐co‐glycolide) microspheres (PLGA MPs). This new injectable drug delivery system can successfully deliver APIs locally, increase drug retention time, and promote endogenous cartilage regeneration. In this study, resveratrol (RSV), a small hydrophobic compound is introduced as the selected API. PLGAs with differing copolymer ratios and endgroups are evaluated to study their effects on particle formation, RSV encapsulation, and drug release kinetics. This system is optimized as a 1 month sustained release formulation. In addition, the long‐acting chondrogenic induction of the RSV‐loaded system is evaluated by coculturing with cartilage‐derived progenitor cells in vitro. PLGA–RSV MPs stimulated the expression of cartilage‐related genes and the production of the cartilage‐specific extracellular matrix. This integrated system shows great potential as an injectable formulation for long‐acting chondrogenesis and endogenous cartilage tissue regeneration. Abstract : An integrated system which consists of a hyaluronic acid (HA)‐based injectable hydrogel scaffold embedded with resveratrol (RSV)‐loaded poly(d, l ‐lactide‐ co ‐glycolide) microspheres (PLGA MPs) is developed. This novel injectable system can provide controlled drug release and stimulating chondrogenesis in vitro for 4 weeks, exhibiting great potential as a long‐acting formulation for fast filling of cartilage defects and facilitating hyaline cartilage generation.